Primary greatness : the 12 levers of success - Covey, Stephen R. (Simon & Schuster, 2015)
"This book is a collection of several of [Sean Covey's] father's best essays that have never appeared in book form before and aren't well known. But they are vintage Stephen Covey and contain some of his best thinking"--Foreword.